Original sin and everyday Protestants : the theology of Reinhold Niebuhr, Billy Graham, and Paul Tillich in an age of anxiety - Finstuen, Andrew S. (Chapel Hill, NC : University of North Carolina Press, 2009)
Finstuen deals with the reception of original sin by the people in the pews. In the years following World War II, American Protestantism experienced tremendous growth, but conventional wisdom holds that midcentury Protestants practised an optimistic, progressive, complacent, and materialist faith. Finstuen argues against this view, showing that theological issues in general - and the ancient Christian doctrine of original sin in particular - became important to both the culture at large and to a generation of American Protestants during a postwar 'age of anxiety' as the Cold War took root.
Introduction -- Protestantism in an age of anxiety : the captive and theological revivals of midcentury -- A curious trinity : the prophet, the evangelist, and the theologian -- Original sin : the only empirically verifiable doctrine of the Christian faith -- Reinhold Niebuhr, America's prophet-pastor -- Billy Graham, America's evangelist -- Paul Tillich, seelsorger in America.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 600
Keywords: Niebuhr, Reinhold, -- 1892-1971.; Graham, Billy, -- 1918-2018.; Tillich, Paul, -- 1886-1965.; Graham, Billy, -- 1918-2018; Niebuhr, Reinhold, -- 1892-1971.; Tillich, Paul, -- 1886-1965.; Tillich, Paul; Niebuhr, Reinhold; Graham, Billy; Sin, Original -- History of doctrines -- 20th century; RELIGION -- Christian Theology -- General; Sin, Original -- History of doctrines; Evangelische Theologie; Erbsünde; Systematische Theologie; USA; 1900-1999; Electronic books